Cerebellar Purkinje cell firing reduction contributes to aging-related declining motor coordination in mice - Eviatar Fields; Ben C. Rogers; Tsz Chui Sophia Leung; Andy Huang; Megan Kern; Nell Kontowicz; Hannah Dolin; Alanna J. Watt (Proceedings of the National Academy of Sciences, 2026)
Aging is associated with the decline of many bodily functions including motor coordination. Aging-related impairment in motor coordination can result in falls, which reduce independence, health span, and quality of life in the elderly. To study the neural mechanisms that underlie this decline, we studied aged mice and observed a progressive decline in motor coordination on multiple motor coordination assays. The cerebellum is critically involved in motor coordination and balance, and cerebellar Purkinje cells play an important role in modulating motor output and coordinated movements. Purkinje cells fire high-frequency and high-regularity action potentials in healthy young adult mice. We wondered whether this firing remained stable across lifespan in aging mice. We performed juxtacellular recordings from Purkinje cells in acute cerebellar slices and observed a reduction in the rate of firing in aged animals without changes in firing regularity. To understand whether reduced Purkinje cell firing rate caused impaired motor performance in aged mice, we used chemogenetics to modulate Purkinje cell firing. Reducing Purkinje cell firing rates in young mice impaired motor performance, while elevating Purkinje cell firing rates in aged mice improved motor performance. Our results suggest that Purkinje cell firing rate impacts motor coordination and that the aging-related reduction of Purkinje cell firing rate that we observed contributes to impaired motor coordination and could contribute to declining health span and quality of life in the elderly.